2014
DOI: 10.1111/jonm.12250
|View full text |Cite
|
Sign up to set email alerts
|

Turkish nurses' assessments of their power and the factors that affect it

Abstract: We recommend that nurses, educators and managers develop strategies to support nurses' power as a way to enhance the patient care outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(46 reference statements)
0
0
2
Order By: Relevance
“…Also, Abou Hashish (2015) reported that nurse managers were more likely to influence their subordinates with tactics of rational persuasion, inspirational appeal, and collaboration, whereas personal appeal and pressure were the least frequently utilized influence tactics. However, the results were inconsistent with Basaran and Duygulu (2015), who found that participants thought that positions gave them influential power. In this respect, we believe that all power bases and influence tactics are distinct and important, and we suggest that no single strategy is all beneficial in influencing nurses.…”
Section: Discussioncontrasting
confidence: 80%
“…Also, Abou Hashish (2015) reported that nurse managers were more likely to influence their subordinates with tactics of rational persuasion, inspirational appeal, and collaboration, whereas personal appeal and pressure were the least frequently utilized influence tactics. However, the results were inconsistent with Basaran and Duygulu (2015), who found that participants thought that positions gave them influential power. In this respect, we believe that all power bases and influence tactics are distinct and important, and we suggest that no single strategy is all beneficial in influencing nurses.…”
Section: Discussioncontrasting
confidence: 80%
“…(25) The study by Bassaran et al also revealed that 44% of nurses believed they had organizational power and only 34% had legal and informative power. (26) The results of this study did not comply with the current study, which can be attributed to the cultural differences, differences in the power structure, the study method and the sample size. This is because Bassaran' study was conducted on Turkish nurses with a different culture than Iranian nurses and the sample size was also larger.…”
Section: Discussioncontrasting
confidence: 70%